2005
DOI: 10.1042/bj20041020
|View full text |Cite
|
Sign up to set email alerts
|

Homotypic dimerization of the actin-binding protein p57/coronin-1 mediated by a leucine zipper motif in the C-terminal region

Abstract: The actin-binding protein p57/coronin-1, a member of the coronin protein family, is selectively expressed in immune cells, and has been implicated in leucocyte migration and phagocytosis by virtue of its interaction with F-actin (filamentous actin). We previously identified two sites in the N-terminal region of p57/coronin-1 by which it binds actin, and in the present study we examine the role of the leucine zipper motif located in the C-terminal coiled-coil domain in mediating the homotypic association of p57… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
35
0

Year Published

2006
2006
2015
2015

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(36 citation statements)
references
References 35 publications
(48 reference statements)
1
35
0
Order By: Relevance
“…The results from western blotting revealed that cross-linking of p57 by DSS led to the appearance of a dimer band (46 kDa, the monomer is 23 kDa) (Figure 4A), which was consistent with the report of Oku et al [8] since no trimer or other higher-molecular-weight band was observed. However, in the p57 297-461/Mut sample, no dimer band was detected ( Figure 4A).…”
Section: After P57supporting
confidence: 81%
See 3 more Smart Citations
“…The results from western blotting revealed that cross-linking of p57 by DSS led to the appearance of a dimer band (46 kDa, the monomer is 23 kDa) (Figure 4A), which was consistent with the report of Oku et al [8] since no trimer or other higher-molecular-weight band was observed. However, in the p57 297-461/Mut sample, no dimer band was detected ( Figure 4A).…”
Section: After P57supporting
confidence: 81%
“…The leucine zipper domain is closely related to the dimerization (or oligomerization) of p57 molecule [8,9]. Therefore, we suppose that the dimerization (or oligomerization) of the p57 297-461 monomers may lead to the conformational change in the region surrounding the actin-binding site, which results in the presence of the actin-binding activity.…”
Section: After P57mentioning
confidence: 99%
See 2 more Smart Citations
“…Recently, gene knockout of coronin-1a in murine T cells leads to reduced ability to respond to chemotactic gradients and also increased susceptibility to apoptotic stimuli (Foger et al 2006). Although the relationship between the actin cytoskeleton and coronin-1a is incompletely understood, these properties have lead researchers to believe that coronin-1a is involved in modulating rearrangement of the actin cytoskeleton during immune-specific functions (Oku et al 2005).…”
mentioning
confidence: 99%